Economic Impact of Etanercept in Patients with Psoriasis and Psoriatic Arthritis in Spain: A Systematic Review - Lluís Puig; Lourdes Rodríguez Fernández-Freire; Ramón Burgos-Pol; Ismael Gomez; Carmen Peral; Susana Gomez; Francisco José Rebollo Laserna (Adis, Springer Healthcare, 2019)
Abstract Introduction Etanercept (ETN), a highly effective biological agent for the treatment of psoriasis (PSO) and psoriatic arthritis (PsA), is widely used in Spain. However, evidence of its economic impact is limited, indicating the need for a systematic review of the economic assessments conducted on the use of ETN in the treatment of both PSO and PsA in Spain. Methods A systematic review was carried out in PubMed, Embase, Cochrane Library, Health Technology Assessment reports and not indexed sources up to November 2018. The inclusion criteria were economic evaluations (total and partial) and dose optimization studies published in English or Spanish on the use of ETN to treat PSO and PsA for ETN in Spain. Results A total of 402 publications were identified, of which 32 were selected for inclusion in the review; of these 32 publications, 81.3% analyzed PSO (14 full economic evaluations, 5 partial economic evaluations and 7 dose optimization studies) and 18.8% analyzed PsA (1 economic analysis and 5 dose optimization studies). The perspective of the Spanish National Health Service (NHS) was used in 90.0% (n = 18) of the full and partial economic evaluations. The time horizons ranged from 12 weeks to 2 years. Reductions in the Psoriasis Area and Severity Index (PASI) of 50, 75 and 90% (PASI 50, 75 and 90, respectively) were most commonly used as efficacy outcomes in the complete evaluations. The economic impact of ETN ranged from €9110-14,337/PASI 75 at 12 weeks (50 mg/week) to €82,279/PASI 90 at 2 years, depending on the health outcome, time horizon and ETN dose used. Only one study determined the cost of using ETN for the treatment of PSO (€29,430-52,367/QALY for dose 2 × 25 mg/week or 50 mg/week, respectively). Only one partial economic evaluation on PSA was identified (NHS perspective), resulting in an ETN annual cost of €8585/patient-year. Conclusion Consistent evidence on the economic impact of ETN for the treatment of PSO and PSA in Spain is lacking, mainly due to the highly heterogeneous methodology used and the broad range of outcomes found in the economic evaluations published to date. Funding Pfizer S.L.U.